Media technologies and science art in the context of modern cultural and art practices - A. M. Tormakhova, (Ukrainian Cultural Studies, 2020)
Media in the 21st Century Cultural Area is an integral component of artistic practices. Currently, a new direction is emerging – science art, which combines art, technology and scientific development. The leading feature of contemporary music is its transformation, which is due to the changing channels of artistic communication that set certain parameters. Music plays a very important role in the space in which it is performed, both the material itself and the musicians. A promising area of science-art development is the emergence of software and equipment that allows us to "resurrect" the stars of the past, simplify the process of musical creation and performance. There is currently a use of holograms for various purposes in music. Sometimes holograms play the role of an accompanying factor, because they can create a background for the performer, replacing the usual scenery, compensate for the absence of dancers, creating a visual basis for performances. Performers working in the field of popular and pop art are often organized in this way. Examples include the concert numbers of participants in the Eurovision Song Contest. Also, hologram or media projection can be used not only as a background but also as a leading factor in a composition. Hatsune Miku is media performer which presents by a hologram and "performs" with live instrumentalists. Miku's visual characteristics are driven by the traditions of manga comics and anime cartoon strips. The vocal party is created using software that can combine different samples. In this case we are talking about the use of the Vocaloid program, which synthesizes the human voice to record vocals, as well as the vocaloid as a fictional character corresponding to a particular synthesized voice. Although Hatsune Miku's live performances are accompanied by live-instrumental performers, the audience's focus is on the vocalist. The ability to create the perfect virtual performers gradually diminishes the professional qualities of gifted live musicians, whose ability is limited, unlike a vocaloid. The evolution and advancement of technology are changing the disposition between composer, performer and audience, but create new opportunities for creative expression.
Keywords: media, music, hologram, science art, creativity, cultural and artistic practices